2020
DOI: 10.1093/ecco-jcc/jjaa085
|View full text |Cite
|
Sign up to set email alerts
|

Enteroids Generated from Patients with Severe Inflammation in Crohn’s Disease Maintain Alterations of Junctional Proteins

Abstract: Background The mechanisms underlying loss of intestinal epithelial barrier [IEB] function in Crohn’s disease [CD] are poorly understood. We tested whether human enteroids generated from isolated intestinal crypts of CD patients serve as an appropriate in vitro model to analyse changes of IEB proteins observed in patients’ specimens. Methods Gut samples from CD patients and healthy individuals who underwent surgery were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
2
30
3
Order By: Relevance
“…This indicated that loss of Dsg2 in CD is maintained in the intestinal regeneration niche or on a stem level respectively. In this study loss of Dsg2 was present on a protein level, whereas Dsg2 mRNA was unaltered indicating a posttranscriptional mechanism leading to loss of Dsg2 in CD 98 . While the detailed mechanisms underlying this observation remain to be elucidated this may support the view that inflammation‐induced barrier defects in CD are not just a secondary phenomenon because of an inappropriate immune response but play a primary role in the pathogenesis of CD 99 .…”
Section: Alterations Of Dsg2 Levels and Desmosome Ultrastructure In Ibdsupporting
confidence: 68%
See 2 more Smart Citations
“…This indicated that loss of Dsg2 in CD is maintained in the intestinal regeneration niche or on a stem level respectively. In this study loss of Dsg2 was present on a protein level, whereas Dsg2 mRNA was unaltered indicating a posttranscriptional mechanism leading to loss of Dsg2 in CD 98 . While the detailed mechanisms underlying this observation remain to be elucidated this may support the view that inflammation‐induced barrier defects in CD are not just a secondary phenomenon because of an inappropriate immune response but play a primary role in the pathogenesis of CD 99 .…”
Section: Alterations Of Dsg2 Levels and Desmosome Ultrastructure In Ibdsupporting
confidence: 68%
“…Interestingly, when enteroids from the same CD patients were generated from crypts that contain the intestinal stem cell niche, loss of Dsg2 was maintained under culture conditions. This phenomenom was observed without cytokine stimulation and was present over several passages of enteroid culture 98 . This indicated that loss of Dsg2 in CD is maintained in the intestinal regeneration niche or on a stem level respectively.…”
Section: Alterations Of Dsg2 Levels and Desmosome Ultrastructure In Ibdmentioning
confidence: 89%
See 1 more Smart Citation
“…Animals were kept on a standard diet and 12-h day and night cycles. To generate organoids, intestinal epithelial cells were isolated from mice intestine as described previously [37].…”
Section: Animals and Intestinal Organoid Generationmentioning
confidence: 99%
“…Quantification of immunostaining was carried out as described previously [37]. In brief, a 10-μm line was placed orthogonal to the cell border with the cell border representing the middle of this line.…”
Section: Quantification Of Immunostainingmentioning
confidence: 99%